Will Indonesia enter the 2023 financial crisis? Application of early warning model system - Anggito Abimanyu; Muhammad Handry Imansyah; Muhammad Adisurya Pratama (Universitas Islam Indonesia, 2023)
Purpose ― This paper estimates the possibility of a financial crisis in Indonesia using an early warning system (EWMS) model. Method ― A quantitative EWMS model has been developed to detect a potential financial crisis in 2023 based on the econometric logistic probability model (Logit) Findings ― Based on the model estimates, Indonesia is expected to enter a financial crisis without adequate macroeconomic policies in the next 12 to 24 months. In recent years, Indonesia has implemented prudent macroeconomic policies such as increasing the Bank Indonesia policy rate and sustaining the state budget to avoid the impact of a deep financial crisis. Implications ― To avoid the potential for further financial crises, Indonesia must implement a wider range of crisis mitigation policies. Originality/value ― Although many argue that financial crises are predictable, it has been demonstrated in the literature that little is known about how to prevent them. This paper contributes to providing empirical evidence to address these issues.